Detection of coronary artery blockage at an early stage using effective deep learning technique - Promit, Tahmid Ashrafee; Khan, Md. Akibur Rahman; Arnob, Nahian; Rashid, Rabbi Nur; Reza, Afif (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.